2007
DOI: 10.1017/s1751731107658030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milking frequency and nutritional level on aspects of the health and welfare of dairy cows

Abstract: The objective of this experiment was to investigate the effect of milking frequency and nutritional level on some aspects of animal health. Holstein-Friesian cows (n ¼ 60) were assigned post calving to a factorial arrangement of treatments; twice a day (TAD) milking on a high or low nutritional level; once a day (OAD) milking on a high or low nutritional level. Milking characteristics were recorded daily. Blood samples to evaluate changes in the composition of the blood cells, milk leakage, udder tension and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 19 publications
7
43
2
Order By: Relevance
“…Teat-end condition deteriorated during lactation; this is partially in contrast with the observations of other authors Gleeson et al, 2007) who reported an increase in teat-end callosity until 4-5 months of lactation and a decrease thereafter.…”
Section: Discussioncontrasting
confidence: 85%
“…Teat-end condition deteriorated during lactation; this is partially in contrast with the observations of other authors Gleeson et al, 2007) who reported an increase in teat-end callosity until 4-5 months of lactation and a decrease thereafter.…”
Section: Discussioncontrasting
confidence: 85%
“…This is presumably due to the increased frequency of milking. Results are similar to the research results of [3]; [6] which states that changes in teat end condition of dairy cattle in older lactation are worse than dairy cow in earlier lactation. Associated with [7] theory which stated that cattle are said to be in a problem if more than 20% of cattle have teat end with rough keratin ring or more than 10% with very rough keratin ring, therefor by looking at Table 1 it can be said that dairy cattle at sixth and seventh lactation faces problems.…”
Section: Teat End Conditionsupporting
confidence: 88%
“…Finally, as there was no difference in the concentration of glucocorticoid metabolites in the faeces with milking frequency before or after the switch, nor any changes in behaviour indicative of discomfort , it is unlikely that the contrasting circadian body temperature rhythms in cows milked 2x or 1x could be interpreted as a sign of physiological stress per se. Other groups have found more lameness and udder firmness early in 1x lactation (Gleeson et al, 2007), and it could be useful to look at body temperature early in lactation or in cows producing more milk, both situations when discomfort might be a greater risk.…”
Section: Discussionmentioning
confidence: 99%
“…Cows milked 1x accumulate a large volume of milk in their udder over 24 h (Davis et al, 1999), which may result in udder distension and compromise their comfort as found at peak lactation by Gleeson et al (2007). Our objective was to investigate milking frequency as a potential physiological stressor in dairy cows milked 2x and 1x at peak lactation, and in response to a change from 2x to 1x at mid-lactation.…”
Section: Introductionmentioning
confidence: 99%